SCALE VALIDITY IN EXPLORATORY STAGES OF RESEARCH - Patricea Elena BERTEA; Adriana ZAIŢ (Management & Marketing)
Scale development assumes that certain steps are to be taken in order to obtain a valid measurement instrument. Most of the researchers jump to the confirmatory stage and avoid exploratory measures. However, exploratory methods that are used in the first stages of scale development are recommended so as to avoid further problems regarding the validity of the scale. Before conducting reliability analysis and factorial analysis, exploratory methods can be applied. The main purpose of this paper is to draw the attention on alternative methods for scale validation that should be used in the exploratory phase. The role of these methods is to improve validity of results of the further confirmatory phases of research. The Lawshe (1975) content validity ratio and the Q-sorting procedure for testing construct validity are applied in the process of developing a scale for perceived risk.